Art 21 art in the twenty-first century 4 - Sollins, Susan; Sollins, Marybeth (New York Abrams, 2007)
Companion book to Art for the Twenty-First Century, the first broadcast series for national television to focus exclusively on contemporary visual art and artists in the United States today.
Keywords: Art, American -- 20th century; Art, American -- 21st century; Artists -- United States -- Interviews; Artists -- United States -- Biography